2016
DOI: 10.1016/j.brat.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and postnatal depression: A systematic review and a cognitive model

Abstract: Postnatal depression (PND) confers risk for a range of negative child developmental outcomes, at least in part through its impact on parenting behaviour. Whilst the behavioural effects of depression on parenting are well established, the cognitive mechanisms that may mediate this effect are less well understood. The current paper proposes that rumination may be a key cognitive mechanism through which parenting is affected in PND, and provides a systematic review of the existing literature on rumination in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 75 publications
2
46
0
1
Order By: Relevance
“…DeJong et al . () developed a testable theoretical model of the effects of rumination on maternal sensitivity during mother–infant interactions. Other environmental pathways by which parental rumination exerts its adverse effects on children's outcomes across different age groups would be a fruitful area of research.…”
Section: Discussionmentioning
confidence: 99%
“…DeJong et al . () developed a testable theoretical model of the effects of rumination on maternal sensitivity during mother–infant interactions. Other environmental pathways by which parental rumination exerts its adverse effects on children's outcomes across different age groups would be a fruitful area of research.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that the tendency to engage in RNT heightens the risk for, and contributes to the maintenance of, post-partum depression has been minimally tested, despite repeated calls for such work [21]. This is surprising given the hypothesised key role for RNT (in the form of rumination) in mediating the impact of maternal psychopathology on parenting [22].…”
Section: Rnt In the Perinatal Contextmentioning
confidence: 99%
“…Moreover, such studies have yielded conflicting findings: some have demonstrated that RNT is predictive, while others have reported no such relationship [21]. For example, Barnum et al [25] found that levels of rumination (brooding) predicted increases in depression symptoms from the third trimester to 8 weeks (but not 4 weeks) post-partum.…”
Section: Potential Roles Of Rnt In the Perinatal Contextmentioning
confidence: 99%
See 2 more Smart Citations